Motor Performance and Skill Acquisition in Oral Motor Training With Exergames: A Pilot Study - Kumar, Abhishek; Munirji, Linda; Nayif, Sam; Almotairy, Nabeel; Grigoriadis, Joannis; Grigoriadis, Anastasios; Trulsson, Mats (Frontiers in Aging Neuroscience, 2022)
Objective: To investigate the effects of oral-motor training with exergames on motor performance and motor skill acquisition in two different age groups. Methods: Thirty-two healthy participants were recruited in the current pilot study and divided equally into two groups (Gen Z and Baby Boomers) according to their age. A pair of electromyographic (EMG) electrodes were placed on the participants’ masseter muscles. The EMG device communicated via Bluetooth with a mobile video game in response to the electromyographic activity of the masseter muscles during clenching. During the experimental session, participants were asked to play a video game in 5 blocks of 5 minutes each, with a 3-minute break between each time block. The goal of the game was to collect as many coins (game points) as possible and to dodge/avoid upcoming obstacles (game life). Motor performance was assessed by performance scores and the number of game lives. Skill acquisition was measured by task efficiency (ratio of performance scores and number of game lives) across time blocks. Results: The results of the study showed significantly lower performance scores (p<0.001), a higher number of game lives (p<0.001), and lower task efficiency in the Baby Boomer group compared to the Gen Z group. Specifically, the results showed that there was a significant difference in task efficiency between the first and second, third and fourth, fourth- and fifth-time blocks in the Gen Z group (p<0.002). However, there was only a significant difference between first- and second-time blocks in the Baby Boomer group (p=1.012), suggesting that skill acquisition in the Baby Boomer group did not change significantly over the course of the time blocks. Conclusion: The study showed higher motor performance and superior motor skill acquisition with novel exergame training in the Gen Z group compared to the Baby Boomer group. The results of the study indicate that there is an improvement in oral motor skills with short-term training, yet the differences in oral motor skills between the two groups are still evident. The Baby Boomer group, unlike the Gen Z group, did not show robust improvement in task efficiency over the course of the series.